2014
DOI: 10.2169/internalmedicine.53.2218
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 256 Cases of Classic Fever of Unknown Origin

Abstract: Objective The causes of fever of unknown origin (FUO) vary depending on the region and time period. We herein present a study of patients with classic FUO where we investigated differences based on patient background factors, such as age and causative diseases, and changes that have occurred over time. Methods We extracted and analyzed data from the medical records of 256 patients ! 18 years old who met the criteria for classic FUO and were hospitalized between August, 1994 and December, 2012. Results The medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
4
18
0
1
Order By: Relevance
“…However, the findings from the current study show almost similar numbers of patients diagnosed with infections and NIIDs. This trend can partly be explained by the exclusion of HIV infected patients, but still comparable to the results from other studies since the 1930's that show a decline in infectious causes of FUO (10,14). The considerable proportion of "unknown" cases in the patient population is also analog to the concerns expressed elsewhere, specifically in the developed world (Horowitz).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, the findings from the current study show almost similar numbers of patients diagnosed with infections and NIIDs. This trend can partly be explained by the exclusion of HIV infected patients, but still comparable to the results from other studies since the 1930's that show a decline in infectious causes of FUO (10,14). The considerable proportion of "unknown" cases in the patient population is also analog to the concerns expressed elsewhere, specifically in the developed world (Horowitz).…”
Section: Discussionsupporting
confidence: 83%
“…Lymphoma is the common malignancy presenting with FUO; a similar pattern has been reported in a previous evaluation in our setting (21). Considering the insidious nature of lymph node involvement in hematologic malignancies, the findings of other studies confirm the same picture (10).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Because ESRD and diabetes mellitus can both lead to an immunocompromised status and increase susceptibility to unusual infections, [19]. In this context, Japanese investigators have reported that the causes of fever of unknown origin (FUO) are infection (27.7 %), non-infectious inflammatory disease (18.4 %), malignancy [20]. Thus, given the frequency of an unknown cause of FUO, we usually use empirical antibiotics to treat infections of unknown origin until culture results are available.…”
Section: Discussionmentioning
confidence: 99%
“…As diagnostic methods and tools are developed, most patients can reach a definite diagnosis. However, it is reported that 7z to 51z of FUO cases remain undiagnosed (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). There are more than 200 causes for FUO (14).…”
Section: Introductionmentioning
confidence: 99%